Strategi Segmentasi Pasar dalam Meningkatkan Penjualan Produk UMKM di Desa Situ Gadung Kabupaten Tangerang - Reza Khairul Hadi; Komarudin Komarudin; Asep Sulaeman (Jurnal PKM Manajemen Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting local economic development, but many face challenges in increasing sales due to limited marketing knowledge. In Desa Situ Gadung, Tangerang Regency, local traders often struggle to identify and target their market effectively, which hinders business growth. This community service activity aimed to improve the marketing capacity of MSME traders by introducing practical market segmentation strategies to enhance product sales. The program was conducted at Tajaul Karomatu School on November 7–8, 2025, and was implemented by three lecturers from Universitas Pamulang, involving 17 local traders as participants. The activity was carried out in three stages: preparation, implementation, and reporting. During the implementation stage, participants engaged in material presentations, practical exercises, group discussions, and question-and-answer sessions to ensure understanding and application of market segmentation principles. The results showed that participants gained a better understanding of identifying target customer groups, customizing products to meet consumer needs, and adopting appropriate promotional strategies for different market segments. They also actively applied these concepts in planning to increase their sales. This initiative not only enhanced the marketing skills of local traders but also promoted community engagement and contributed to sustainable economic development in Desa Situ Gadung.